Use of heuristic methods in performing practical tasks in design disciplines - Omelchenko, Olga (Professional Art Education, 2021)
The purpose of the article is review, analysis and practical coverage of heuristic methods in the performance of control practical tasks in design disciplines.Methods & methodology. Based on the principle of the sequence of consistent information, methods of heuristic analysis, interpretation and stylization, the method of associations, the effectiveness of training designers in higher educational institutions is determined, creative search is activated, skills of graphic, plastic, figurative, integral form formation are developed.The scientific novelty of the article lies in the definition and specification of a set of heuristic methods that can more effectively influence the process of training future designers, help to reveal students’ individual abilities, develop artistic thinking, taste, imagination, and courage to experiment.Results. The essence of heuristic learning methods in the performance of practical tasks in design disciplines is revealed. A set of tasks from the course "Fundamentals of composition" (color science, form formation) using heuristic methods (heuristic analysis, interpretation and stylization, method of associations, etc.) are highlighted. Examples of creating three-dimensional compositions through development ideas and options for transforming dots into lines, lines into spots, spots into volume with the use of meter and rhythm are provided. The effectiveness of the presented tasks in creating decorative compositions from any materials and techniques has been proven: stained glass, tapestry, appliqué, intarsia, painting, sketches of an abstract mini collection of clothes, etc.The use of heuristic methods (heuristic analysis, interpretation and stylization, the method of associations, etc.) in the performance of practical tasks on the basics of composition (color science, form formation) helps to find individual abilities in a student, to reveal and develop artistic thinking, taste, imagination, courage to experiment, without which creative activity of the designer is impossible. The effectiveness of the presented tasks is determined in the creation of decorative compositions from any materials and techniques: stained glass, tapestry, appliqué, intarsia, painting, sketches of an abstract mini collection of clothes, etc.
Keywords: design; composition; heuristics; heuristic methods; form formation; color science